Analisis Pelayanan Publik Menggunakan Customer Relationship Management Model - Sela Taramita; Zena Lusi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the need to develop digital services to enhance the quality of electronic government-based services at the Population and Civil Registration Office (Disdukcapil) of Palembang City. The study applies the Customer Relationship Management (CRM) model to 10 public service areas available on the official Disdukcapil website. The variables analyzed include commitment to information technology (IT), IT-related communication, service quality, and customer satisfaction in utilizing digital services. The research uses a descriptive quantitative approach, with data collected through a Google Form questionnaire distributed via WhatsApp to Palembang City residents. Data analysis using SPSS confirmed that the questionnaire was valid, and the reliability test produced a Cronbach's Alpha of 0.982, exceeding the standard of 0.7, indicating high consistency. Further analysis using AMOS revealed that customer satisfaction reached 95% for the commitment variable, 94% for communication, and 95% for service quality. Overall, the study indicates that customer satisfaction with the digital services of Palembang City Disdukcapil is categorized as good. These findings provide insights and practical recommendations for the government to improve the design and implementation of electronic government services, aiming to increase efficiency, responsiveness, and citizen satisfaction in public service delivery.